PENGARUH TAYANGAN NET 10 TERHADAP PENINGKATAN MINAT MAHASISWA UNTUK MENJADI SEORANG CITIZEN JOURNALISM - Rahayu, Wayan Nopi; Sudaryanto, Edy; Rochim, Achludhin Ibnu (representamen, 2016)
NET 10 is a one of news program, thatâ€™s also give a lot of information goingaround the people whoâ€™s in through Citizen Journalism segments. People whoâ€™s seeingthe interested things can record it and then just upload to the NET.CJ, and the last thebest video will showing at Citizen Journalism segment on NET 10. Based on these, theauthors are interested to take title â€œThe Effect Of NET 10 Show For The IncreasedInterest Of Student To Become A Citizen Journalismâ€. This study used a quantitativeresearch methods with data retrieval technique using a questionnaire distributed to 63students of communication science class 2015 as research samples. The data analysisusing SPSS to test the validity, reliability, correlation coeficient test, coeficient andsimple linear test, regression analysis techniques. There are two variables : X variables(NET 10 Show) and Y variables (The Increased Interest of Student). Analysis of theresult is concluded that the study result are significant and have a sufficient correlationwhere the correlation result showed the number 0,303 with significant value 0,016 <0,05. Based on the results of this analysis, the impressions NET 10 (X variables) is hasenough to effect the increased interest of student.Keyword : NET 10 show, interest, Citizen Journalism.